Gadolinium-enhanced MRI reveals dynamic development of endolymphatic hydrops in Ménière's disease - Li,Xuanyi (2020)
Abstract Introduction: Meniere's disease is associated with impaired hearing, tinnitus, vertigo, and aural fullness. Many anatomical studies have suggested idiopathic endolymphatic hydrops as the pathological basis of Meniere's disease, which now can be visualized by using gadolinium -enhanced magnetic resonance imaging of the inner ear. Objective: To investigate the development of endolymphatic hydrops in Meniere's disease by monitoring the vestibules and cochleae of affected patients. Methods: Inner ears of 178 patients with definite unilateral Meniere's disease diagnosis were visualized by 3-dimensional fluid-attenuated inversion recovery and three-dimensional real inversion recovery magnetic resonance imaging following bilateral gadolinium intratympanic injection. The scans were used to evaluate the presence and degree of endolymphatic hydrops in the vestibules and cochlear structures, including the cochlear apical turn, the cochlear middle turn, and the cochlear basal turn. The correlation of endolymphatic hydrops occurrence between the various parts of the inner ear was determined. Results: Symptomatic endolymphatic hydrops was detected on the affected side in all patients, whereas asymptomatic endolymphatic hydrops was detected on the unaffected contra-lateral side in 32 patients (18.0%). On the affected side, the cochlear apical turn and the cochlear middle turn demonstrated significantly higher rates of endolymphatic hydrops than the cochlear basal turn and the vestibule. The severity of endolymphatic hydrops gradually decreased from the cochlear apical turn to the cochlear basal turn. On the contra lateral side, the incidence and degree of the detected asymptomatic endolymphatic hydrops were significantly greater in the cochleae than in the vestibules (p < 0.05), with no significant difference detected between the cochlear turns. Conclusion: Progression of endolymphatic hydrops appears to be directional, initiated in the cochlea. The order of endolymphatic hydrops severity gradually decreases from the cochlear apical turn to the cochlear basal turn and then to the vestibule. Endolymphatic hydrops in the vestibule is associated with symptomatic Meniere's disease.